2018
DOI: 10.3892/ijmm.2018.3887
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Annexin A1 suppressed the apoptosis and inflammatory response of preeclampsia rat trophoblasts

Abstract: Preeclampsia (PE) is a disorder that is characterized by pregnancy-induced hypertension. It has been reported that Annexin A1 (ANXA1) is highly expressed in the plasma of women diagnosed with PE. Therefore, the present study aimed to examine the effect of ANXA1 on PE rats. The PE animal model was constructed in rats using Nω-nitro-L-arginine methyl ester (L-NAME), and the blood pressure and urine protein levels of rats were detected. The pathological features of placental tissue, and the levels of inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Annexin A1 is a phospholipid-binding, Ca 2+ -dependent protein regulating cell behavior by inhibiting autophagy (63), enhancing inflammation and apoptosis (14, 63), suppressing proliferation (43), etc. In the ECM, conflicting reports implicate annexin A1 in both improving fibroblast synthetic activity (26) and exerting antifibrotic effects (38), potentially suggestive of a context-dependent function for this molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Annexin A1 is a phospholipid-binding, Ca 2+ -dependent protein regulating cell behavior by inhibiting autophagy (63), enhancing inflammation and apoptosis (14, 63), suppressing proliferation (43), etc. In the ECM, conflicting reports implicate annexin A1 in both improving fibroblast synthetic activity (26) and exerting antifibrotic effects (38), potentially suggestive of a context-dependent function for this molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this study, the expression of pro-caspase-3 and pro-caspase-9 showed a slight increase in certain cells however no cleavage of these caspases was observed. Feng et al demonstrated that silencing of ANXA1 reduced apoptosis by upregulating Bcl-2 and procaspase-3 levels while downregulating the expression of cleaved caspase-3 in trophoblasts from preeclampsia rat's placenta tissue (16). The cleavage of caspase-9 and caspase-3 in this study was not observed probably due to approximately 10 min of caspase activation when there was a trigger of cell destruction.…”
Section: Mechanism Of Apoptosis In Cells Transfected With Sirna For Anxa1mentioning
confidence: 43%
“…Although the exact reason has been unclear, recent reports suggested that suppression of ANX A1 expression interferes with apoptotic cell death in several cell lines. [44][45][46] These suggest that systematic disruption of ANX A1 expression in mice may contribute to protect against the CCl4induced cell death in the liver via distinct mechanisms from ANX A1 activation by sesamin metabolites. Based on the current results, a model for the mechanism of action of SC1 in monocytes is illustrated (Fig.…”
Section: Discussionmentioning
confidence: 96%